Farm machinery - Culpin, Claude (Frogmore, St Albans Granada publishing ltd., 1976)
First published in 1938, this remains the leading work on agricultural engineering and farm mechanism for students, farmers, advisers and the agricultural engineering industry.
includes index
occ 17/01/2019
Loans
Keywords: Agricultural machinery; Farm mechanization